JAMBUWANTRAO DHOTE’S CONTRIBUTION TO MAHARASHTRA POLITICS - Saosakade, Nitesh Devrao; Nande, Praful Vitthalrao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Jambuwantrao Dhote was interested in politics since his school life. While studying in college, he decided to do public welfare work. He had formed his organizations to solve the problems of people like farmers, agricultural laborers, workers, auto drivers, tong drivers, owners. Through this organization, Dhote tried to solve the problems of workers, farmers, agricultural laborers. Through administration, he was taking the problems of the people to the government and getting them resolved. While studying in college, he had closely observed the political changes taking place in the then Indian situation. During this period, the Samyukta Maharashtra movement was gaining momentum. Naturally, Jambuwantrao Dhote participated in the movement. Through this movement, he became aware of the politics of the country. In the Samyukta Maharashtra movement, he disrupted the meetings of Vidarbha activists. He was actively involved in the Samyukta Maharashtra movement. Due to his aggressiveness, he was expelled from the college. But his passion for politics and the problems of the people did not allow him to sit idly by. He was not happy with this job as a physical education teacher in the municipal council school. He started working to solve the problems occurring in the cities of Yavatmal. He became their leader by solving the problems of the Kolam, tribal and Dalit people in Yavatmal city. After this, Dhote contested the Yavatmal Nagar Panchayat election and entered local politics. Due to the immense support of the people, Jambuwantrao Dhote became famous in Yavatmal district within a short period of time. The people preferred him as a candidate for the Legislative Assembly and he became the MLA of Yavatmal. He traveled his political life from a member of the Nagar Panchayat to an MLA of the Maharashtra Legislative Assembly, an MP of the Lok Sabha and a king maker who formed the government. After 1985, he was constantly away from power politics. He devoted his entire life to the movement for an independent Vidarbha state.